2007
DOI: 10.1007/s10669-007-9069-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual changes in human EEG caused by 450 MHz microwave modulated at 40 and 70 Hz

Abstract: This study was aimed to investigate the changes in the human electroencephalographic (EEG) signal caused by modulated low-level microwaves. The 450 MHz microwave exposure modulated at 40 Hz and 70 Hz frequencies was applied to a group of 15 volunteers. The field power density at the scalp was 0.16 mW/cm 2 . Ten cycles of the exposure (1 min on and 1 min off) at both modulation frequencies were applied. Analysis of the EEG signal was performed using three different methods: nonlinear method of scaling analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The results of this study are in good agreement with the rate of individual sensitivity 13-31% reported in our previous publications (Hinrikus et al 2008a;Bachmann et al 2007). It seems that inter-hemispheric asymmetry as a measure for evaluation of the microwave effect on EEG has about the same sensitivity as relative changes in the EEG power.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are in good agreement with the rate of individual sensitivity 13-31% reported in our previous publications (Hinrikus et al 2008a;Bachmann et al 2007). It seems that inter-hemispheric asymmetry as a measure for evaluation of the microwave effect on EEG has about the same sensitivity as relative changes in the EEG power.…”
Section: Resultssupporting
confidence: 92%
“…In previous studies the individual sensitivity to microwave exposure was evaluated based on relative changes in the EEG power (S-parameter) (Hinrikus et al 2008a;Bachmann et al 2007). The results of this study are in good agreement with the rate of individual sensitivity 13-31% reported in our previous publications (Hinrikus et al 2008a;Bachmann et al 2007).…”
Section: Resultssupporting
confidence: 89%
“…It appears that the most intriguing are papers on animal brain exposure (Salford et al 2007;Ushiama et al 2007). The results of studies in the last decade (Leszcynski et al 2002;Bachmann et al 2007) demonstrated alteration in EEG in humans.…”
Section: Radiofrequency Electromagnetic Fields In the Environmentmentioning
confidence: 99%
“…The powers of four basic EEG frequency bands, theta (4-6.8 Hz), alpha (8)(9)(10)(11)(12)(13), beta1 (15)(16)(17)(18)(19)(20) and beta2 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), were extracted from the total EEG (0.5-48 Hz) by filtering. Elliptic bandstop filters with an attenuation of 50 dB in the stopband were used.…”
Section: Resting Eeg: Preprocessingmentioning
confidence: 99%
“…In this paper we present an overview and analysis of the main results of papers [ 7,8,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Investigations were aimed first of all to the selection and development of methods, sensitive to small hidden changes in the EEG signal.…”
Section: Introductionmentioning
confidence: 99%